Granular transfer molding of multimodal powders - Shin, H; Kim, J; Lee, HW; Lee, J; Kim, SW; Song, H (ELSEVIER SCI LTD, 2004)
Relatively homogeneous green compacts were prepared with the powders of multimodal particle size distribution by granular transfer molding (GTM) Using the premixed granules. The homogenous granules were prepared by rapid granule formation by solvent exchange even with multimodal powders. In order to obtain optimum green microstructure, it is necessary to control resin migration and granule deformation with the help of resin Solubility and molding temperature. The process mechanism of granular transfer molding could be divided into Four steps: granule arrangement under external field, local deformation of granules accompanied by individual particle packing, resin curing in the presence of a liquid vehicle, and liquid removal. (C) 2003 Elsevier Ltd and Techna S.r.l. All rights reserved.
Keywords: SILICON; INFILTRATION; COMPOSITES